Analysis regarding the reduction of the amount of fuel used in the combustion process to reduce polluting emissions - Lupchian, Mariana (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
In the paper, the consumption of fuels and lubricants is calculated according to the operating regimes of the naval energy installation. Consumption was analyzed from the perspective of reducing polluting emissions. The fuel and lubricating oil for the main engine and auxiliary engines were determined. The study was done for several navigation situations.